Accounting for anxiety : an analysis of an early first-century material ethic from Matt 6:19-34 - Tryon, Denzil Bruce (Stellenbosch : Stellenbosch University, 2008)
Thesis (MTh (Old and New Testament))--Stellenbosch University, 2006.